Pengaruh Model Pembelajaran Group Investigation (GI) Terhadap Hasil Belajar Biologi Pada Materi Ekosistem - Diana, Diana; Anisa, Anisa (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2024)
This research is a pre-experimental research which aims to determine the effect of using the Goup Investigation (GI) model on the learning outcomes of class X MAs Darunnajah Botong students on ecosystem material with a "one-group pretest-posttest designs" research design. The population in this study was class X MAS Darunnajah Botong which consisted of one class. The sample for this research was all class X students selected using saturated sampling. The research variables consist of the independent variable, namely the Group Investigation (GI) model, while the dependent variable is student learning outcomes. Data collection was carried out through administering a pretest-posttest. The technique used uses two methods, namely descriptive data analysis techniques and inferential data analysis techniques (normality test, homogeneity test and hypothesis test). Test the hypothesis using the Anova test and paired sample t-test with the Statistical Package For Social Science (SPSS) program for Windows version 25. The student learning outcome scores before implementing the Group Investigation (GI) learning model were in the less than 86.6 category after implementation Group Investigation (GI) learning model, student learning outcomes are in the fair category at 53.3% and in the good category at 20%, more than that there are students who reach the very good category at 13.3%. Keywords: Group Investigation (GI), Learning Outcomes